The IGS Standard Operating Procedure for Automated Prokaryotic Annotation. Issue 2 (March 2011) - Galens, Kevin; Orvis, Joshua; Daugherty, Sean; Creasy, Heather; Angiuoli, Sam; White, Owen; Wortman, Jennifer; Mahurkar, Anup; Giglio, Michelle
Abstract The Institute for Genome Sciences (IGS) has developed a prokaryotic annotation pipeline that is used for coding gene/RNA prediction and functional annotation ofBacteria andArchaea . The fully automated pipeline accepts one or many genomic sequences as input and produces output in a variety of standard formats. Functional annotation is primarily based on similarity searches and motif finding combined with a hierarchical rule based annotation system. The output annotations can also be loaded into a relational database and accessed through visualization tools.